Application of the high-density resistivity method in detecting a mined-out area of a quarry in Xiangtan City, Hunan Province - Jia, Xie; Yang, Liu; Yulong, Lu; Lianzhi, Zhang (Frontiers in Environmental Science, 2022)
Goaf ground collapse has great constraints on people's lives, property safety, and social development within the influence scope because of its concealment and suddenly happening characteristics. The high-density resistivity method is used to explore the goaf of a quarry in Xiangtan City, Hunan Province. The surface subsidence of the goaf is analyzed by the apparent resistivity inversion section diagram and the comprehensive analysis results. The filling water or sediment in the goaf is reflected as a low resistivity abnormal body, which is significantly different from the resistivity change of the surrounding bedrock and the contour fluctuation. The morphological characteristics and geological conditions of the underground abnormal body in the goaf are deduced. Based on the geophysical prospecting method, the geological disasters such as goaf ground collapse can be explored. Combined with the analysis and processing of inversion data, the geological structure and stratum information of goaf can be inferred, which provides a theoretical basis for further disaster prevention.